2012
DOI: 10.1007/s10571-012-9895-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leukemia Inhibitory Factor on the Myelinogenic Ability of Schwann-Like Cells Induced from Human Adipose-Derived Stem Cells

Abstract: The Schwann cells (SCs) may be obtain from nerve biopsies for autologous transplantation. However, it is difficult to obtain sufficient amount of SCs for clinical applications. Human adipose-derived stem cells (ADSCs) can be induced to differentiate into Schwann-like cells (S-like cells) and used for autologous transplantation. However, effect of leukemia inhibitory factor (LIF) on the myelinogenic ability of SC-like cells induced from human ADSC is not investigated yet. The aim of this study was to evaluate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It is determined these isolated cells are stem in the previous study. [24] The cell cultures were kept at a temperature of 37°C in a humid atmosphere with 5% CO 2 . The medium was changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…It is determined these isolated cells are stem in the previous study. [24] The cell cultures were kept at a temperature of 37°C in a humid atmosphere with 5% CO 2 . The medium was changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…ADSCs can be induced and differentiated into Schwann cells-like cells in vitro [22, 23]; in this research, the differentiated cell expresses both S-100 and GFAP that exist in Schwann cells. At the same time, it have been observed that ADSCs can adhere and grow in the scaffold when they were implanted into the acellular nerve scaffold; during this period, the cytoactivity of them was similar to the cells in culture media ( P > 0.05); it means good histocompatibility between cells and acellular nerve scaffold [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Zavan et al [2010] showed that proliferating glial-like cells could be isolated from human neurospheres. This method has been adapted and, with the inclusion of leukemia inhibitory factor in the differentiation medium, it was possible to increase the number of S100/GFAP-positive cells and the percentage of myelinating cells [Razavi et al, 2013]. A greater understanding of the mechanisms behind the induction of Schwann cell gene and protein expression is required to develop more effective differentiation protocols for human stem cells.…”
Section: Adsc and Schwann Cell Differentiationmentioning
confidence: 99%